The first case report of infective endocarditis caused by Gemella taiwanensis. Issue 8 (August 2017) - Hikone, Mayu; Sakamoto, Naoya; Ota, Masayuki; Washino, Takuya; Kobayashi, Ken-ichiro; Iwabuchi, Sentaro; Kazama, Haruko; Kounosu, Akiko; Negishi, Kumiko; Ainoda, Yusuke; Iguchi, Shigekazu; Yoshida, Atsushi; et al.
Abstract: Gemella is a facultative anaerobic Gram-positive coccus and a rare cause of infective endocarditis (IE). Gram staining may eventually misidentify the organism, which tends to easily decolorize and manifest as either Gram-negative or Gram-variable. Commercial biochemical tests are often used to identify Gemella, but the methods they employ sometimes lack accuracy. A 52-year-old woman was diagnosed with Gemella taiwanensis IE after initial identification of the pathogen as Gemella haemolysans using biochemical tests combined with matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). She was treated successfully with penicillin, gentamicin, and mitral valve replacement. To our knowledge, this is the first case of IE confirmed by 16S rRNA gene and groEL sequencing to have been caused by G. taiwanensis . The accurate diagnosis of rare or difficult-to-identify pathogens is a major challenge for clinical microbiological laboratories. The concurrent use of molecular methods could lead to the recognition of new or different pathogens.